Polymyalgia Rheumatica After Herpes-Zoster - Fazıl KULAKLI; Sevgi KULAKLI; İlker İLHANLI and Sevinç ASLAN and Elif UYSAL and Canan ÇELİK (Archives of Rheumatology, 2018)
Polymyalgia rheumatica (PMR) is a systemic disease associated with widespread body pain, in the elderly.(1) Herpes zoster (HZ) is characterized by painful vesicular rash with dermatomal distribution.(2) Although it causes many complications, to our knowledge, PMR secondary to HZ has not been previously reported. A 64-year-old female patient who was suffering from severe pain in her shoulders and legs for two weeks was admitted to our clinic. Her pain was very intense in the mornings and the Visual Analog Scale pain score was 10. The patient explained that she began to suffer from pain in the right ear and throat with accompanying rash around the ear two weeks ago. She was diagnosed with HZ by the dermatology department and valaciclovir 500 mg 3x2 was started. On the fifth day of treatment, shoulder and leg pain started and peaked on the 10th day. No pathology was found in rheumatologic examination. She stated that one of her three sons had Behçet’s disease, the other had familial Mediterranean fever and the third one had acute rheumatic fever. The patient had no history of any chronic systemic disease. Upper extremity movements were normal but painful. There was diffuse swelling and extreme sensitivity with palpation on lower extremities. The movements of lower extremities were also painful. There was no scalp tenderness or headache. The pulses of the temporal arteries were normal. White blood cell (19300/mm(3)), erythrocyte sedimentation rate (93 mm/hr) and C-reactive protein (47 mg/L) values were elevated in the laboratory tests. She had a consultation with an infectious diseases clinic but no infection focus was found. As a result of all evaluations, the patient was diagnosed with PMR and methylprednisolone 16 mg/day was started. A dramatic clinical response was obtained. A significant decrease was observed in the laboratory parameters by the seventh day (white blood cell: 10400/mm(3), C-reactive protein: 0.60 mg/L, erythrocyte sedimentation rate: 52 mm/hr) and the Visual Analog Scale score was 3. Although the exact cause of the disease is unknown, some infectious agents such as Mycoplasma pneumoniae, Chlamydia pneumoniae, and Parvovirus B19 may cause PMR.(1) In addition, the literature includes cases of giant cell arteritis (GCA) and PMR after influenza vaccination.(3) The relationship between varicella zoster virus (VZV) and GCA remains unclear and the association between VZV and PMR has never been discussed in the literature before. There are few studies that do not support the hypothesis of the GCA development after VZV reactivation.(4,5) Contrary to these studies, VZV antigen was detected in temporal arteries of patients with GCA in a study.(6) Another study reported that VZV is a risk factor for the development of GCA. In this study, it was suggested that PMR and GCA were similar diseases and HZ could also cause PMR, so PMR patients were excluded from the study.(7) In our case the patient was not diagnosed with GCA. However since PMR and GCA share similar pathophysiologic mechanisms, we also think that HZ may play a role in the development of PMR as noted in the article by England et al.(7)